The costs of justice : how new leaders respond to previous rights abuses - Grodsky, Brian K., 1974- (Contemporary European politics and society., 2010)
""An insightful, profound, and conceptually innovative analysis of the daunting challenges encountered by the new democracies in their endeavors to confront the traumatic past. Grodsky's comparative approach allows him to highlight similarities and differences between states, institutions, and elites engaged in pursuing political and moral justice. A most valuable contribution to the major ongoing debate on the relationship between democracy, history, memory, and justice."--Vladimir Tismaneanu, University of Maryland" ""Brian K. Grodsky seeks to understand the sources of diversity in transitional justice processes and, by implication, a broad range of post-conflict policy making. He develops and empirically evaluates a theoretical framework, relying on extensive original primary research and cross-national fieldwork---all things that have traditionally been lacking in much of the relevant transitional justice literature, until recently. The Costs of Justice is situated on the cutting edge of the field."-David Backer, The College of William & Mary" "In the Costs of Justice, Brian K. Grodsky provides qualitative analyses of how transitional justice processes have evolved in diverse ways in postcommunist Poland, Serbia, Croatia, and Uzbekistan. By examining the decision-making processes and goals of those actors who contributed to key transitional justice policy decisions, Grodsky challenges the argument that transitional justice in post-repressive states is largely a function of the relative power of new versus old elites. He maintains that a new regime's transitional justice policy is more closely linked to its capacity to provide goods and services expected by constituents, than to political power struggles alone. In introducing this goods variable, so common to broad political analysis but largely overlooked in the transitional justice debate, Grodsky argues that we must revise our understanding of transitional justice."--Jacket